PENERAPAN TEORI KONSTRUKTIVISTIK PADA PEMBELAJARAN BAHASA ARAB DI KELOMPOK 28 PROGRAM INTENSIFIKASI BAHASA ARAB IAIN SYEKH NURJATI CIREBON - Hikmah Uswatun Ummi; Indrya Mulyaningsih (Jurusan Tadris Bahasa Indonesia, 2016)
Use appropriate teaching methods teachers' creativity. Learning foreign languages, especially Arabic Arabic Intensification Program IAIN Sheikh Nurjati Cirebon using various methods. Inquiry method, question and answer, and the group is a method of teaching according to the constructivist approach. Constructivist theory of learning understood as the process of formation (construction) knowledge by the learners themselves. Interest in constructivist theory encourages authors to observe the application of constructivist theory in a group of 28 Intensification Program Arabic IAIN Syekh Nurjati Cirebon. Results observation is that the Arabic language learning in a group of 28 Intensification Program Arabic IAIN Syekh Nurjati Cirebon approach constructivism theory.